Pengaruh Penggunaan Media Pembelajaran Flash Card Terhadap Kemampuan Belajar Kognitif Siswa Kelas II Sekolah Dasar - Suhartati, Apria; Lian, Bukman; Kuswidyanarko, Arief (Institut Teknologi Pendidikan Indonesia, 2022)
The purpose of this study was to determine the effect of using flashcard learning media on the cognitive learning abilities of second-grade elementary school students. The method of this research is to use the Pre-Experimental Design experimental method. The population in thisstudy were all class II students at SD Negeri 31 Palembang for the 2021/2022 academic year, while the sample in this study were students of class II. As an experimental class, which consisted of 21 students. Data collection techniques in this study use observation, tests, and documentation. While the data analysis technique uses the t-test, based on the results of the study it can be concluded that it is 4.82 > the value of 1.72. Thus it can be concluded that it is rejected and accepted or there is an influence from the application of the use of flash card learning media on the cognitive learning abilities of class II elementary school students.